Gastrectomy with omentum preservation versus gastrectomy with omentectomy for locally advanced gastric cancer: A systematic review and meta-analysis. (December 2021) - Chen, Mi; He, Fu-Qian; Liao, Mao-Shan; Yang, Chao; Chen, Xiao-Dong
Abstract: Background: Omentectomy has been traditionally a part of standard radical gastrectomy. Its clinical benefit for locally advanced gastric cancer (LAGC) remains controversial. This study aimed at evaluating the impact of gastrectomy with omentum preservation (GOP) on survival, recurrence, surgical outcomes and postoperative complications by comparing with gastrectomy with omentum resection (GOR). Methods: Original studies comparing GOP with GOR in LAGC were searched. Meta-analysis was performed using RevMan 5.4. Results: Seven studies involving 1879 patients were analyzed. Compared with GOR, GOP achieved significantly better overall survival (HR = 0.75 [0.60, 0.95], P  = 0.01), with similar relapse-free survival (HR = 0.84 [0.68, 1.03], P  = 0.10). The two groups had similar total recurrence rate (OR = 0.86 [0.68, 1.08], P  = 0.19) and no significant differences in rates of peritoneal, hematogenous, locoregional or distant lymph node recurrences. GOP had significantly less blood loss (MD = −83 [-139, −28] ml, P  = 0.003) and tended to have shorter operation time (MD = −28 [-58, 2] min, P  = 0.06), with similar harvested number of lymph nodes (MD = −0.4 [-2.6, 1.8], P  = 0.70). The incidences of total all grade and major complications were similar in GOP and GOR (all grade: 31.8% vs. 30.3%, OR = 1.08 [0.79, 1.46], P  = 0.64; major: 9.2% vs. 10.1%, OR = 1.14 [0.55, 2.34], P  = 0.73). There were no significant differences in incidences of complication or postoperative mortality. Conclusions: Omentum preservation did not affect curability or survival in LAGC. These findings require validation in randomized controlled trials with large sample sizes. Graphical abstract: Image 1 Highlights: Clinical benefit of omentectomy for advanced gastric cancer remains controversial. Omentum preservation may not decrease curability or survival. Randomized controlled trials are ongoing and anticipated.